KEANEKARAGAMAN MAKROZOOBENTOS SEBAGAI INDIKATOR KUALITAS PERAIRAN DANAU SIOMBAK KECAMATAN MEDAN MARELAN KOTA MEDAN The Diversity of Macrozoobenthic as Water Quality Indicators of Siombak Lake District of Medan Marelan in Medan City - Achmad Taher Daulay; Darma Bakti; rusdi leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Siombak is the artificial lake formed as the result of sand dredging activities in an area formerly known as Paya Pasir. The purpose of this study was to determine the water physical and chemical parameters of Siombak Lake in conjunction with water quality standards at PP 82 Tahun 2001 and Storet methods as well as the diversity of macrozoobenthic.This study was conducted from May to July 2014 at the Siombak Lake District of Medan Marelan in Medan City. The results obtained, the relationship between water chemical physical parameters of Siombak Lake in reference to water quality standards at PP 82 Tahun 2001 and Storet method states that the waters of Siombak Lake belong to the C class with the condition of water being moderately contaminated.The value of diversity index (H') of macrozoobenthic were obtained at each station study ranged from 1,091 to 1,480. The results of Pearson correlation analysis showed that temperature, COD, phosphate, light penetration and BOD5 have a positive correlation with the diversity of macrozoobenthic while salinity, DO and nitrate have a negative correlation.Keywords: Siombak lake, Diversity of Macrozoobenthic, Water Quality